PEMANFAATAN MEDIA ONLINE DALAM PEMASARAN PRODUK KULINER DI PRIANGAN TIMUR: PEMANFAATAN MEDIA ONLINE DALAM PEMASARAN PRODUK KULINER DI PRIANGAN TIMUR - Santi Susanti; Iwan Koswara (Jurnal Kajian Budaya dan Humaniora, 2024)
COVID-19 has had a significant impact on aspects of human life in the world. The economic sector is among those affected. Many business people are forced to close their businesses because they cannot produce, due to the lack of purchasing power, including MSMEs. The existence of the internet is a solution to keep the economy running. Many entrepreneurs then utilize social media, as a channel for promoting and marketing their products so that they remain known by potential buyers until the transaction process occurs. This study aims to reveal the efforts of MSME culinary business actors in the East Priangan region, utilizing social media as a promotional and marketing medium, to maintain their business in the COVID-19 pandemic situation. The research methods used are interviews with culinary MSME players in East Priangan, observation, and the use of online data sources obtained through social media. The results showed that social media helped MSME players in the East Priangan region in running their businesses in the COVID-19 situation. Instagram and Whatsapp are most widely used in online sales. Sales through social media are almost equivalent to direct sales. The conclusion of this study is that social media is a solution in increasing the sluggishness of product sales during the COVID-19 pandemic.